Wanting and Liking: Testing the Factor Structure of The Temporal Experience of Pleasure Scale in Major Depression and Community Samples. (July 2022) - Hallford, David John; Austin, David W.
The Temporal Experience of Pleasure Scale (TEPS) is a multidimensional self-report measure that has been used to improve understanding of anticipation ("wanting") and consummation ("liking") of reward. The TEPS has been used to assess anhedonia in clinical depression, but its factor structure has not yet been confirmed in this population. This seems important given mixed findings on the model fit and factor structure of the TEPS in other clinical and community samples. To remedy this, the current study used confirmatory factor analysis to test models of the TEPS items across three studies: (a) in adults with major depression ( n = 334), (b) in youth with major depression ( n = 305), and (c) in a community sample ( n = 320). In summary, the model fit of the two-factor TEPS scales was adequate in depressed and community Australian samples. Nevertheless, some items may require removal or revision based on cultural preferences for pleasurable experiences.